2021
DOI: 10.1111/jfpp.15844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation time and temperature on the of polyphenol compounds change of different Congou black tea

Abstract: Black tea is among the most popular beverages worldwide, accounting for ~78% of the world's total tea produced, consumed, and traded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Therefore, it can be concluded that the contents of TPC and TFC were attributed to the antioxidant capacity of brown rice products. The results are consistent with the findings of Aguilar-Garcia et al [ 39 ] and Chmiel et al [ 26 ], who also reported a strong correlation between total phenolic content and antioxidant activity of rice bran.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it can be concluded that the contents of TPC and TFC were attributed to the antioxidant capacity of brown rice products. The results are consistent with the findings of Aguilar-Garcia et al [ 39 ] and Chmiel et al [ 26 ], who also reported a strong correlation between total phenolic content and antioxidant activity of rice bran.…”
Section: Resultssupporting
confidence: 93%
“…The increment of TPC in cooked GBR due to the activation of cell wall-degrading enzymes and phenylalanine ammonia lyase upon germination resulted in the release and biosynthesis of phenolic compounds [ 21 ]. In addition, the breakdown of cell wall structure caused by fermentation also leads to the synthesis of phenolic compounds [ 26 ]. However, the TPCs of bound fractions in cooked GBR were the highest, while in EBR the lowest.…”
Section: Resultsmentioning
confidence: 99%
“…TPs were determined by the Folin–Ciocalteu colorimetric assay (GB/T 8313-2018) with slight modification using GA as a standard [ 33 ]. Briefly, 0.20 g of black tea powder was mixed with 5 mL of 70% ( v/v ) methanol and ultrasonically extracted (SB-5200DT; Scientz, China) twice at room temperature for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, more clinical studies are needed to elucidate the specific mechanisms. A recent study demonstrated that the content of MAF‐2 in Congou black tea gradually increased (up to 5.11%) with the increase in fermentation time and temperature, which may be related to the activity of polyphenol oxidase and peroxidase during the fermentation process (Wu, Ozawa, et al., 2021). (5)Polymethoxyflavonoids (PMFs) …”
Section: Special Tea Products Featuring Other Chemical Componentsmentioning
confidence: 99%
“…Caffeine and theobromine exhibit similar chemical structures and physiological activities, such as exerting preventive effects on cardiovascular diseases, cancer, neurodegenerative diseases, and respiratory diseases. However, theobromine alleviates dentin hypersensitivity and enamel damage (Wu, Tong, et al, 2021).…”
Section: Theobromine-rich Tea Productsmentioning
confidence: 99%